Influence of high school grade point average on university performance: a case study from Albania - Karma, Emiljan; Dautaj, Mitat (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aimed to investigate the impact of high school grade point average (GPA), as an admission criterion, on university performance using administrative data from a non-profit private university in Albania. This paper also examines additional variables that may influence the final degree outcome at Catholic University Our Lady of Good Counsel (Tirana). An ordinal regression analysis was conducted to forecast university performance based on selected university characteristics across various degree courses for 1,485 graduates. The study indicates that the high school GPA, which serves as an entrance requirement for Albanian universities, has a partially insignificant impact on the final university degree. Other factors, such as nationality, gender, university grade point average, and time required for graduation, directly and significantly affect the degree outcome. This result has implications for the efficiency of high school GPA as a mandatory university access criterion. At the same time, the negative impact of high school GPA as a mere barrier to university access is highlighted.